2008
DOI: 10.1590/s0100-204x2008000200015
|View full text |Cite
|
Sign up to set email alerts
|

Atributos físicos do solo e produtividade de milho em resposta a culturas de pré-safra

Abstract: Resumo -O objetivo deste trabalho foi avaliar os atributos físicos de um Latossolo Vermelho distrófico argiloso e a produtividade de milho em sistemas de manejo que incluem plantas de cobertura cultivadas em pré-safra (setembro a novembro). Foram utilizadas, durante quatro anos, as seguintes plantas de cobertura: crotalária (Crotalaria juncea); milheto (Pennisetum americanum sin. tiphoydes); lab-lab (Dolichus lablab) em sistema de semeadura direta; e pousio cultivado em sistema de preparo convencional, anteced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 17 publications
(17 reference statements)
2
8
0
6
Order By: Relevance
“…Ceres, Viçosa, v. 59, n.6, p. 859-866, nov/dez, 2012 system showed higher values of geometric mean diameter in the layers 0-0.05, 0.05-0.10 and 0.10-0.15 m, and for mean weight diameter in the layers 0-0.05 and 0.05-0.10 m, compared with the conventional planting, which agreed with Calegari et al (2006), who observed the same trend. However, within the type of management itself, it was found that, the depth increases with the diameter of the aggregates, which corroborates the data of Sousa Neto et al (2008) and Salton et al (2008) These authors found that this behavior is due to the organic matter content of the soil, because there is a decrease in the amount of this cementing agent of aggregates with increasing depth.…”
Section: Resultssupporting
confidence: 84%
“…Ceres, Viçosa, v. 59, n.6, p. 859-866, nov/dez, 2012 system showed higher values of geometric mean diameter in the layers 0-0.05, 0.05-0.10 and 0.10-0.15 m, and for mean weight diameter in the layers 0-0.05 and 0.05-0.10 m, compared with the conventional planting, which agreed with Calegari et al (2006), who observed the same trend. However, within the type of management itself, it was found that, the depth increases with the diameter of the aggregates, which corroborates the data of Sousa Neto et al (2008) and Salton et al (2008) These authors found that this behavior is due to the organic matter content of the soil, because there is a decrease in the amount of this cementing agent of aggregates with increasing depth.…”
Section: Resultssupporting
confidence: 84%
“…Souza Neto et al (2008) contribuem no entendimento desse fenômeno ao afirmarem que a Ds é um atributo que pode indicar condições restritivas ao desenvolvimento radicular, em função da umidade do solo, da resistência à penetração e do espaço poroso do solo.…”
Section: Resultsunclassified
“…The absence of correlation between the OC availability with GMD and the soil aggregate classes was also found by Almeida et al (2014). However, in the soil there may also be more aggregate stability promoted by increased organic material accumulation (Beutler et al, 2001;Souza et al, 2008).…”
Section: Resultsmentioning
confidence: 99%